Hubungan Kualitas Tidur Terhadap Kadar Hemoglobin pada Calon Pendonor di Unit Donor Darah PMI Provinsi Sulawesi Selatan - Adinda Ashari; Hairuddin K; Dahniar Dahniar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Blood transfusion requires the availability of high-quality blood, which is determined, among others, by the donor's hemoglobin (Hb) level. One factor that may affect Hb is sleep quality. Objective: This study aims to determine the relationship between sleep quality and hemoglobin levels among prospective blood donors at UDD PMI South Sulawesi Province in 2025. Methods: An observational analytic study with a cross-sectional design was conducted involving 100 respondents selected using purposive sampling. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), while Hb levels were measured using a hemoglobinometer. Data analysis was performed using the Chi-Square test with a significance level of p ≤ 0.05. Results: The majority of respondents (75%) had good sleep quality, while 25% had poor sleep quality. Normal Hb levels (12.5–17 g/dL) were found in 96% of respondents, while 3% were low and 1% were high. The Chi-Square test showed a significant relationship between sleep quality and Hb levels (p = 0.050). Conclusion: Good sleep quality is significantly associated with normal hemoglobin levels in prospective donors. Educational programs about healthy sleep patterns before donation are necessary to improve donor eligibility and ensure a safe blood supply.